Prevalence of gastrointestinal nematodes in alpacas and sheep from two communal cooperatives in the Pasco region, Peru - Puicón, Víctor (2018)
The aim of this study was to determine the prevalence of gastrointestinal nematodes in Huacaya alpacas and Corriedale sheep. Between February 2014 and April 2016, 238 faecal samples of alpacas and 319 of sheep were collected in San Pedro de Racco and 215 fecal samples of sheep and 178 samples of alpacas in Yurajhuanca. The faecal count of nematode eggs was determined by the modified McMaster technique and the identification of the parasitic genera through the morphometric identification of infective larvae (L3). The general prevalence was 65.2% (208/319) and 21.4% (51/238) for nematodes in sheep and alpacas of the San Pedro de Racco cooperative, and of 35.4% (76/215) and 3.9% (7/178) for nematodes in sheep and alpacas of the Yurajhuanca cooperative, respectively. The species found in sheep and alpacas from both cooperatives were Oesophagostomum columbianum, Trichostrongylus columbiformis, and Teladorsagia circumcincta.